Aecjusz, ostatni Rzymianin - Parnicki, Teodor (Warszawa : Pax, 1977)
An historical novel at the end of the Roman Empire circa 430.
Continued by Smierc Aecjusza.
Keywords: Rome -- History -- Empire, 284-476 -- Fiction